Work your money, not your life : how to balance your career and personal finances to get what you want - Ma, Roger (Financial planner) (John Wiley & Sons, Inc., 2020)
"When the life people are living and the life people want to live don't match up, they may feel stressed or off-balance. People naturally try to solve the immediate issue they think is causing this uneasiness. If they're stressed about money and falling behind, they may buy one of the many personal-finance books in the market. If they're unhappy with their jobs, they may grab a book on how to find the right career. For those seeking more meaning in their lives, they might opt for a book on mindfulness. In the current state, readers are forced to comb through several books and topic areas to try to connect the dots, which can be extremely difficult. This book seeks to solve that problem by providing readers with actionable advice on how they can find the right career path and determine their desired lifestyle, while teaching them the financial strategies they'll need to make their path a reality. Because people often ignore or deprioritize their personal finances in favor of other pursuits, the book begins by demonstrating how money affects every other part of our lives and how effective money management can empower readers to find a meaningful career and create a satisfying personal life"--